2001
DOI: 10.1007/pl00007898
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of the vascular supply in the rabbit ciliary body by transscleral diode laser cyclophotocoagulation

Abstract: The vascular casting technique is an excellent method for the investigation of changes in ciliary body vascularization after cyclodestruction. This study is the first to demonstrate a marked rarefication of the ciliary body vascularization after diode laser cyclophotocoagulation using vascular casts. The results suggest that alteration of vascularization probably acts as a strong synergistic mechanism in the decrease of intraocular pressure after cyclophotocoagulation of the pars plicata.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 23 publications
3
13
0
2
Order By: Relevance
“…Multiple studies suggest that this is likely the case. Coagulation of the stroma and vasculature of the ciliary body was noted histologically in this study as well as in studies of laser effects on the ciliary body in rabbits . In dogs, ciliary body necrosis and hemorrhage were documented at 7 days and ciliary body atrophy and fibrosis at 28 days after TSCPC .…”
Section: Discussionsupporting
confidence: 53%
“…Multiple studies suggest that this is likely the case. Coagulation of the stroma and vasculature of the ciliary body was noted histologically in this study as well as in studies of laser effects on the ciliary body in rabbits . In dogs, ciliary body necrosis and hemorrhage were documented at 7 days and ciliary body atrophy and fibrosis at 28 days after TSCPC .…”
Section: Discussionsupporting
confidence: 53%
“…19 The laser tip of the G-probe was placed at the limbus since the pigmented rabbit's ciliary processes are located more anteriorly than in the human. [20][21][22] Seven to eight shots were applied over the 100 degrees of limbus.…”
Section: Diode Tcpmentioning
confidence: 99%
“…Each eye was imaged for pre-treatment blood flow, treated, and imaged again within 1 hour post-treatment. The eyes were also imaged at other time points ranging from 12-118 days to study potential vascular remodelling observed elsewhere [2].…”
Section: Treatment Protocolsmentioning
confidence: 99%
“…Elsewhere it has been shown that blood flow can be significantly reduced or completely stopped in cutaneous blood vessels smaller than 30 µm after exposure to pulsed laser radiation [3]. Another study using diode laser CPC showed significant alterations in microcasts of rabbit ciliary body microvasculature, including vessel rarefaction and destruction [2]. Extrapolation of these results to blood flow in ciliary processes suggests that it will be significantly reduced following laser CPC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation